Report of the Committee on Fertilisers - Planning Commission (Planning Commission, 1965)
In the context of non-availability of adequate organic manures providing the necessary soil nutrients, the only way in which manorial requirements can be met is by- the use of chemical fertilisers. India’s agricultural production programme is very much dependent on increased fertiliser use. Our present level of application which was 3.46 Kg. per hectare in 1962-63 is very low. (Paragraphs 1.01 to 1.03)
Ministry of Food and Agriculture (Department of Agriculture)
Ministry of Food and Agriculture (Department of Agriculture) Government of India